Finfish and shellfish diversity of Dholai Fishing Harbour, Gujrat: Biodiversity Conservation status - Ritesh V Borichangar; Sheetal K. Bharda; Rajesh B. Vala; Haresh G. Solanki; Jesing G. Vanza; Mihir R. Patel; Prakash P. Patel; Anand Verma; Krishna Patel (Journal of Indian Fisheries Association, 2022)
The study on marine fish diversity at the Dholai fishing harbour, Navsari, Gujarat, was carried out over a five-year period from January 2016 to December 2020. Random sampling has been carried out throughout the five-year of study period. The fishing harbour exhibits rich fish diversity, with a total 136 finfish and shellfish, belonging to 63 families, and 23 orders. With 33 species, the order Acanthuriformes outnumbered all other orders followed by Carangiformes (26 species), Decapoda (17 species), Clupeiformes (11 species), Perciformes (9 species), Scombriformes (7 species), Siluriformes, Tetraodontiformes (4 species each) Beloniformes (3 species), Carcharhiniformes, Myliobatiformes, Anguilliformes, Atheriniformes, Aulopiformes, Centrachiformes, Elopiformes, Syngnathiforme, (2 species each) and the rest of the orders with a single species. Acanthuriformes and Carangidae were the most dominant order and family comprising 24.26% and 8.82%, respectively. The maximum number of fish species recorded in 2020, the year of the COVID pandemic, was noted. Fish species were classified as threatened or non-threatened based on the IUCN as follows: 05.15% were listed as threatened (01.47% Critically Endangered, 01.47% Endangered, 02.21% Vulnerable), whereas 94.85% as non-threatened (04.41% Near Threatened, 55.15% Least Concern, 10.29% Data Deficient, and 25.00% Not Evaluated). This document offers a groundbreaking and comprehensive checklist of finfish and shellfish at Dholai fishing harbour, Southwest coast of Gujarat.